Quantitative determination of clobetasone butyrate in bulk and cream formulation by a validated stability-indicating reversed-phase HPLC method - Alhazmi, Hassan Ahmad; Manoharan, Gunasekar; Al Bratty, Mohammed; Javed, Sadique Akhtar (European Journal of Chemistry, 2018)
A simple isocratic reversed-phase HPLC method for quantification of clobetasone in bulk and cream dosage forms has been developed. Chromatographic analysis was accomplished on an C18 column utilizing a mixture of methanol and water (84:16 v:v, pH = 6.0) as mobile phase. An effluent flow rate of 1 mL/min was adjusted and the detection was made at 240 nm wavelength. The method was evaluated according to ICH guidelines Q2 R1 for linearity, specificity, sensitivity, precision and accuracy. The method exhibited good linearity with correlation coefficient (r2) of 0.9993 over the concentration range from 5 to 50 μg/mL. The recoveries of the test drug from the cream sample was found to be 98.56 to 99.51% and the limit of detection and quantification were calculated as 0.85 and 2.83 μg/mL, respectively, suggesting the accuracy and sensitivity of the developed method. The precision was demonstrated by a low percentage of relative standard deviation (<1%) from six independent assay analysis performed for the cream formulation. Stability indicating property of the proposed method was demonstrated by performing the analysis of forced degradation samples. The developed method can be used for estimation of the clobetasone butyrate in bulk and pharmaceutical formulations for routine analysis in the quality control laboratories.